The Albanian organization and organizational structure - the challenges of the adaptation to the dynamic reality - Shkurti, Ludmilla (Journal of Education Culture and Society, 2020)
There were 78 400 enterprises active in Albania in 2011, employing 180 800 people, of which 47% worked in 1,684 enterprises employing more than 20 people. These last enterprises represented 61 percent of the total turnover, and 75 percent of the total investments. These enterprises are predominantly in the industrial and construction sectors. Enterprises with 1-4 employees represent 91 percent of the total enterprises, and represent 14 percent of total turnover. Small enterprises are dominant in the service sector. Business in Albania is currently operating in a global environment, which has a great impact on the theory or practice of organizations, and also on the working behaviour of employees. This already complex environment, which is becoming increasingly dynamic, and growing competition, are also changing the way in which work is organized, as well as the solutions. Great opportunities are arising from a better understanding of Albanian contemporary organizations and the work environment. To take advantage of these opportunities, the trends regarding the relationship between organizational design and design work should be studied and identifi ed. The aim is to identify the potential patterns and the current trends and tendencies in Albanian organization design, providing useful knowledge in the fi eld of Albanian business practices, and future challenges for research in this direction.